Proceedings 2019 Network and Distributed System Security Symposium 2019
DOI: 10.14722/ndss.2019.23288
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Attacks Against Automatic Speech Recognition Systems via Psychoacoustic Hiding

Abstract: Voice interfaces are becoming accepted widely as input methods for a diverse set of devices. This development is driven by rapid improvements in automatic speech recognition (ASR), which now performs on par with human listening in many tasks. These improvements base on an ongoing evolution of deep neural networks (DNNs) as the computational core of ASR. However, recent research results show that DNNs are vulnerable to adversarial perturbations, which allow attackers to force the transcription into a malicious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
157
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 36 publications
0
157
0
Order By: Relevance
“…They also showed that such samples could be played over-the-air and even transfered to another commercial black-box speech model. In addition, [44] use psychoacoustic hiding method to inject command into audios and attack Kaldi without human realization. Our work differ with them as our attack could compromise Amazon Echo and can be launched in a long range.…”
Section: Related Workmentioning
confidence: 99%
“…They also showed that such samples could be played over-the-air and even transfered to another commercial black-box speech model. In addition, [44] use psychoacoustic hiding method to inject command into audios and attack Kaldi without human realization. Our work differ with them as our attack could compromise Amazon Echo and can be launched in a long range.…”
Section: Related Workmentioning
confidence: 99%
“…The CTC-loss between the target phrase and the network's output is backpropagated through the victim neural network and the MFCC computation, to update the additive adversarial perturbation. The adversarial samples generated by this work are quasi-perceptible, motivating a separate work [30] to minimize the perceptibility of the adversarial perturbations using psychoacoustic hiding.…”
Section: Related Workmentioning
confidence: 99%
“…Adversarial attacks are a well-known vulnerability of neural networks [24]. For instance, a self-driving car can be tricked into confusing a stop sign with a speed limit sign [9], or a home automation system can be commanded to deactivate the security camera by a voice reciting poetry [22]. The attack is carried out by superposing the innocuous input with a crafted perturbation that is imperceptible to humans.…”
Section: Introductionmentioning
confidence: 99%